Patriarchy and the “Other” in the Western imagination: Honour killings and violence against women - Train, Kelly (International Journal of Child, Youth and Family Studies, 2021)
The purpose of this article is to explore the pedagogical challenges of teaching university-level, feminist, anti-racist courses that examine how Eurocentric patriarchal practices of male violence against women within Canadian society are normalized and obscured through the concept of honour killing. I argue that the normalization of Western structures and practices of patriarchy reproduces racism, sexism, and classism by focusing attention on the “Otherness” of non-Western forms of patriarchy. Honour killings are rendered as distinct from other forms of male violence against women on the basis that they are seen solely as a product of non-Western cultures and religions and not as part of a spectrum of forms of male violence against women practised by all patriarchal societies in Western and non-Western countries.